2019
DOI: 10.4236/jct.2019.103017
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of miRNA-155 Expression on Treatment Outcome in Adult Acute Myeloid Leukemia Patients

Abstract: Background: Acute myeloid leukemia is a heterogeneous hematologic malignancy associated with gene mutations, chromosomal rearrangements, deregulation of gene expression and epigenetic modifications. The treatment outcome of AML is highly variable signifying the heterogeneous nature of the disease. Aim of the Study: To evaluate miRNA-155 expression level as a prognostic marker for adult patients with acute myeloid leukemia. Patients and Methods: 101 subjects were included in this study. They were classified int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 20 publications
(32 reference statements)
0
4
1
Order By: Relevance
“…In the opposite side of our result, [14] reported that there wasn't significant correlation with miR-155 expression level and LDH without giving any explanation.…”
Section: Discussioncontrasting
confidence: 84%
See 4 more Smart Citations
“…In the opposite side of our result, [14] reported that there wasn't significant correlation with miR-155 expression level and LDH without giving any explanation.…”
Section: Discussioncontrasting
confidence: 84%
“…Marcucci [5] reported that at diagnosis of AML cases, high miR-155 expressers had higher percentages of peripheral blood and BM blasts than low expressers with a (P= 0.004 and < 0.001 respectively). Elgohary [14] also reported that there was high significant differences between high and low miR-155 expression levels as regards the percentage of both BM and peripheral blood blast cells (p = 0.006 each). In our study we found that there were no significant correlations between miR-155 gene expression level and age, sex, hemoglobin concentration and platelets count in AML group (P>0.05), this came in concordance with [18] and [14].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations